Adsorpsi Ion Logam Cu(II) Menggunakan Lignin dari Limbah Serbuk Kayu Gergaji - Lelifajri, Lelifajri (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2010)
Adsorption of heavy metal ion Cu(II) onto modified lignin from sawdust waste have been presented. The ability of lignin from sawdust waste to adsorb the copper ion has been evaluated by varying adsorption time, pH of solution, and adsorption capacity. The concentration of copper ion was measured by atomic adsorption spectrometer. The result showed that the optimum condition of ion Cu(II) by lignin were achieved at adsorption time of 15 minutes, pH of solution of 6, and copper concentration of 20 mg/L with adsorption efficiency of 99,3 %. In this study, the maximum capacity of 15,43 mg/g and equilibrium constant of 754,96 were achieved.Keywords: adsorpsi, ion tembaga, lignin, limbah serbuk kayu gergaji